Crosstalk‐Free Mesa‐Etched Passive‐Matrix Microscale Light‐Emitting Diode Array Using Yttrium‐Iron Garnet P‐Type Resistive‐Switching Electrodes. Issue 3 (29th December 2022) - Kim, Jun Young; Lee, Ho Jin; Son, Kyung Rock; Yu, Min Ji; Hong, Seok Hee; Kim, Tae Geun
Abstract: Microscale light‐emitting diodes (µLEDs) have ushered in a new era of small‐sized high‐resolution displays by integrating numerous microscale pixels within a limited panel area. However, to realize passive‐matrix‐based high‐resolution µLED displays, it is important to prevent image diffusion (crosstalk) between the pixels. Herein, p‐type resistive‐switching (RS) electrodes are introduced in a mesa‐etched passive‐matrix‐based µLED array structure to block electrical interference between adjacent pixels and eliminate cross‐talk. To distinguish between addressed and unaddressed pixels in the µLED array structure, the resistance state of the RS electrode is modulated from low (52 Ω) to high (1.2 × 10 7  Ω). Moreover, the RS electrode exhibits a high on/off ratio (10 6 ), good retention (10 5  s), and stable endurance (10 4 cycles). X‐ray photoelectron spectroscopy analysis reveals that the switching mechanism in the RS electrodes is achieved by the generation and annihilation of oxygen vacancies in the conductive path. Consequently, the fabricated µLEDs with RS electrodes exhibit a 93.1% higher electroluminescence intensity and 95.3% higher light output power compared to a reference device fabricated through combined mesa‐ and isolation‐etching. Abstract : Electrical crosstalk in passive‐matrix microscale light‐emitting diode (µLED) arrays is eliminated by introducing yttrium iron garnet‐based resistive‐switching electrodes. On/off switching of the µLED pixels is realized through precise control of conductive paths in the resistive‐switching layer by generating and annihilating oxygen vacancies. This enables the implementation of a compact driving circuit by removing the space required for pixel isolation.